Does Chronic Ankle Instability Influence Knee Biomechanics of Females during Inverted Surface Landings? - Li, Yumeng; Ko, Jupil; Walker, Marika; Brown, Cathleen; Schmidt, Julianne; Kim, Seock-Ho; Simpson, Kathy (International Journal of Sports Medicine, 2018)
The primary purpose of the study was to determine whether atypical knee biomechanics are exhibited during landing on an inverted surface. A seven-camera motion analysis system and two force plates were used to collect lower extremity biomechanics from two groups of female participants: 21 subjects with chronic ankle instability (CAI) and 21 with pair-matched controls. Subjects performed ten landings onto inverted and flat platforms on the CAI/matched and non-test limbs, respectively. Knee and ankle joint angles, joint angular displacements, joint moments and eccentric work were calculated during the landing phase and/or at the initial contact. Paired t-tests were used to compare between-group differences (p<0.05). We observed that CAI group displayed a significantly increased knee flexion angle, knee flexion displacement, peak knee extension moment and internal rotation moment, and eccentric work in the sagittal plane, possibly due to altered ankle biomechanics. Participants with CAI employed some compensatory strategy to improve their ankle and postural stability during landing onto the tilted surface. The increased knee extension and internal rotation moments of CAI participants could potentially result in a greater ACL loading. In future studies, it may be worthwhile to measure or estimate the ACL loading to confirm whether CAI could relate to the mechanism of ACL injury.
Keywords: lower extremity; kinetics; kinematics ankle sprains; ACL injuries